A Simple, Inexpensive, and Precise Photographic Method for Intraoperative Toric IOL Alignment - Gerding, Heinrich; Somfai, Gabor Mark; Langenegger, Marco (Klinische Monatsblätter für Augenheilkunde, 2019)
Background It was the aim of this study to analyse the refractive outcome of toric intraocular lens (t-IOL) implantation guided by a newly developed method of photographic alignment.Material and Methods Fourteen eyes of 10 patients (6 females, 4 males, age 63.4 ± 6.7 (40.6 – 68.0) years [mean ± 1 SD (range)]) were included in this retrospective study. All eyes received an Oculentis Tplus LS-313 (Oculentis, Berlin, Germany) t-IOL after standard phacoemusification (n = 4) or femtocataract laser-assisted surgery (n = 10). Image-guided t-IOL alignment included: (1) calculation of t-IOL parameters (combination of different biometric methods) and plotting a layout drawing of the target lens position, (2) capture of an anterior segment slit lamp photograph in the upright position, (3)  superposition of the photographs by the t-IOL target plot and a gradual scale, (4) drawing of marker lines on the photograph and removal of the IOL target coordinates, (5) transfer of the final image to a tablet PC, and (6) marking of the target axis at the corneal limbus with an ink pen in the surgical room.Results Preoperative corneal astigmatism was 2.50 ± 0.97 (1.38 – 4.34) diopters (D) (mean ± 1 SD, range). In all eyes, intraoperative alignment could easily be performed using the photographic target layout. Surgical interventions and postoperative follow-up were without complications in all cases. Residual postoperative astigmatism was 0.16 ± 0.24 (0.00 – 0.75) D (p < 0.001 compared to preoperative astigmatism). In 64% of patients, residual subjective astigmatism was zero, in 93% ≤ 0.5 D, and in 100% ≤ 0.75 D. Postoperative uncorrected logMAR visual acuity (0.05 ± 0.07, range 0.00 – 0.20) and best-corrected visual acuity (0.03 ± 0.05, 0.00 – 0.10) were significantly better (each p < 0.001) than best-corrected preoperative visual acuity (0.21 ± 0.14, 0.00 – 0.49).Conclusions Results of this clinical series clearly indicate that the newly developed photographically guided technique of toric lens alignment leads to highly accurate postoperative results for astigmatic correction.
Keywords: toric intraocular lenses; astigmatism; lens alignment; cornea; intraocular lens; IOL; keratometry; aberrometry